The swamp monster - Dixon, Franklin W. (Dixon, Franklin W. Hardy boys mystery stories, 1985)
The Hardy brothers go to Big Thicket, Texas, to investigate attempts on the life of a naturalist trying to preserve the area wildlife in the face of threats from timber and oil interests.